Microwave Ablation Compared With Laser Ablation for Treating Benign Thyroid Nodules in a Propensity-Score Matching Study - Shi, Yi-Fan; Zhou, Ping; Zhao, Yong-Feng; Liu, Wen-Gang; Tian, Shuang-Ming; Liang, Yong-Ping (Frontiers in Endocrinology, 2019)
Objective: The efficacy and safety of percutaneous ultrasound-guided microwave and laser ablation(MWA and LA, respectively), for treating benign thyroid nodules (BTNs), were retrospectively compared. Methods: Patients (n = 318) underwent ablation of 328 BTNs. Confounding bias was reduced by propensity-score matching, and finally the MWA and LA groups each comprised 160 nodules. At baseline (before ablation), 3, 6, and 12 months, and every 6 months thereafter, the following were recorded: nodule volume reduction rate (VRR), neck symptom scores, cosmetic scores, complications and side effects. Results: The baseline characteristics of the MWA and LA groups were comparable. The volumes of all nodules were less at all follow-ups relative to the baseline, as were the symptom and cosmetic scores at postoperative 6 months and thereafter (P < 0.01). At each follow-up, the overall VRRs of the MWA and LA groups were comparable. However, for nodules ≥13 mL, the VRR associated with LA at ≥6 months was significantly greater than that of MWA. The average ablation time for MWA was less than that of LA (P < 0.01). The overall incidences of major complications, minor complications, and side effects were 1.6%, 2.2%, and 18.4%, respectively, and there were no significant differences between the MWA and LA groups. Conclusion: Percutaneous ultrasound-guided LA and MWA are safe and effective for the treatment of BTNs. Each can significantly reduce the nodule volume and improve the neck symptoms and appearance of patients, with a low incidence of adverse side effects. The efficiency of MWA is higher than that of LA. For nodules ≥13 mL, MWA may be preferred, but at 6 months and subsequent follow-ups the reduction in volume was greater in patients receiving LA.